Excision of Congenital Rhabdomyoma of the Left Outflow Tract through the Left Atrium and Mitral Valve - Lucio Careddu; Francesco Dimitri Petridis; Emanuela Angeli; Giorgio Romano; Valentina Agostini; Antonietta Fucà; Andrea Donti; Gaetano Gargiulo (EL-Med-Pub, 2018)
Primary rhabdomyomas obstructing the right or left outflow tract are uncommon findings in the perinatal period. The presenting symptom may be arrhythmia, cardiac murmur, complete or variable atrioventricular block, pericardial effusion, cardiomegaly, cardiac failure, or sudden death. The variety of symptoms can be explained on the basis of obstruction of blood flow, myocardial involvement, and disturbance of the cardiac rhythm. Commonly, rhabdomyoma spontaneously regresses in the majority of cases, and neonatal surgery is advocated only in case of severe left ventricular outflow tract (LVOT) obstruction or the development of arrhythmias. Herein, we describe the pathologic and clinical characteristics of neonatal presentation of a cardiac rhabdomyoma with a nearly obstructive mass in the LVOT, discovered during pregnancy and operated 4 months after delivery.